Enhancing Colonoscopy Preparation in Elderly Constipation Patients: A Personalized Approach with PEG and Exercise - A Case Study - Zhang L; Huang L; Liu S; Sun X (International Medical Case Reports Journal, 2024)
Lanlang Zhang,1 Lixia Huang,2 Shanshan Liu,3 Xiaofeng Sun4 1Department of Haemodialysis, Fuyong People’s Hospital of Baoan District, Shenzhen, Guangdong Province, 518103, People’s Republic of China; 2Department of Gastrology, Fuyong People’s Hospital of Baoan District, Shenzhen, Guangdong Province, 518103, People’s Republic of China; 3Nursing Department, Fuyong People’s Hospital of Baoan District, Shenzhen, Guangdong Province, 518103, People’s Republic of China; 4Department of Ultrasound, Shenzhen Baoan Women’s and Children’s Hospital, Shenzhen, Guangdong Province, 518000, People’s Republic of ChinaCorrespondence: Xiaofeng Sun, Department of Ultrasound, Shenzhen Baoan Women’s and Children’s Hospital, Shenzhen, Guangdong Province, 518000, People’s Republic of China, Tel +86-13723457417, Email 350787457@qq.comAbstract: This study aimed to optimize bowel preparation efficacy for colonoscopy in elderly constipation patients. A 71-year-old patient with chronic constipation and a history of poor bowel preparation. To address these challenges, we implemented a personalized strategy combining of PEG administration and walking exercise. The PEG was administered according to a protocol, with intermittent exercise breaks of 10 minute. Bowel cleanliness was assessed using the Boston Bowel Preparation Scale (BBPS). Adverse reactions and tolerance were closely monitored throughout the intervention. The patient’s BBPS score improved from 3 to 8 post-intervention. The exercise intervention was well-tolerated (rating I), and mild nausea was observed only after the first PEG dose. No severe adverse reactions occurred. Subsequent Follow-up revealed symptom relief. The personalized approach combining (PEG and exercise intervention) successfully improved bowel preparation quality in the elderly constipation patient undergoing colonoscopy. This approach considers age-related changes in gastrointestinal function and activity level, offering an effective strategy to improve patient tolerance and reduce adverse reactions during bowel preparation. The findings underscore the importance of tailoring interventions for elderly constipation patients to optimize the colonoscopy experience.Keywords: compound polyethylene glycol electrolyte powder, exercise intervention plan, bowel preparation, colonoscopy, elderly, constipation